DAMPAK WANITA KARIR BAGI KELUARGA PERSPEKTIF HUKUM ISLAM - Edy Setyawan; Adang Djumhur; Astri Nurhayati Triana Dewi (IAIN Syekh Nurjati Cirebon, 2022)
The position between men and women should not be a common thing, even the difference between men and women in work is no longer in question, so women are no longer considered, so women are no longer considered as figures in charge of taking care of children, husbands and households only. In accordance with the development of the times make society change its perspective on the role and position of women who are in the midst of society, so many men and women who have careers in modern life many women can work and have a career well in social, cultural, economic and political. The study aims to answer the question that formulaizes the problem: